ANALISA TEORI ACTORS PADA PEMBERDAYAAN MASYARAKAT MELALUI ZAKAT PRODUKTIF DOMPET DHUAFA - Muthohar, Ah Riza; Ahmad, Hany Fatihah (Jurnal Kommunity Online, 2025)
In Islam, there are two types of zakat: consumptive zakat which takes the form of distributing aid fordaily needs; and productive zakat in the form of business capital and is projected to stand alone. Theutilization of zakat in amil institutions also varies. One of them is Dompet Dhuafa as an Islamicphilanthropic organization based on Zakat, Infaq, Alms and Waqf (ZISWAF) which has succeeded ininitiating and giving birth to programs to alleviate poverty and empower the community. Thisresearch aims to determine the extent of the influence of the Dompet Dhuafa empowerment programon its beneficiaries by fulfilling aspects of the ACTORS Theory (Authority, Confidence andCompetence, Trust, Opportunities, Responsibility, and Support). This research uses a qualitativemethod using phenomenology which has three data collection techniques. First, observe DompetDhuafa's programs. Second, using interview techniques for sources and beneficiaries. Finally,documentation by taking pictures in the field. The research results show that the beneficiaries of theDompet Dhuafa programs are slowly becoming empowered. This is demonstrated by the conditionof the beneficiaries who initially had the status of mustahik with the profession of casual workers,slowly becoming empowered by receiving business capital, regular training and mentoring so thatthey have the provisions to then be able to build their own businesses. Researchers use ACTORSTheory to uncover Dompet Dhuafa's empowerment programs.